2015
DOI: 10.5032/jae.2015.02043
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Dimensions and Essential Elements of Exemplary Local Extension Units

Abstract: Collaborative efforts between federal, state, and local government agencies enable local Extension units to deliver a high level of educational opportunities to local citizens. These units represent land-grant institutions by delivering non-formal education that aim to address local, regional, and state concerns. The purpose of this study was to establish consensus that defines the characteristics of an exemplary local Extension unit of the Cooperative Extension Service. This effort is significant because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Dalkey and Helmer's ( 1963) Delphi technique was used to explore the research objectives of this study. The Delphi method is based on a group communication (Terry & Osborne, 2015) and consensus-building process (Ludwig, 1997) that facilitates the research of a "phenomenon that cannot be directly tested or observed" (Costello & Rutherford, 2019, p. 1). Usually beginning with open-ended questions (Terry & Osborne, 2015), the Delphi technique involves a panel of experts who participate in repeated questioning (Dalkey & Helmer, 1963) for the purposes of gathering useful (Costello & Rutherford, 2019, p. 1), agreed-upon information.…”
Section: Methodsmentioning
confidence: 99%
“…Dalkey and Helmer's ( 1963) Delphi technique was used to explore the research objectives of this study. The Delphi method is based on a group communication (Terry & Osborne, 2015) and consensus-building process (Ludwig, 1997) that facilitates the research of a "phenomenon that cannot be directly tested or observed" (Costello & Rutherford, 2019, p. 1). Usually beginning with open-ended questions (Terry & Osborne, 2015), the Delphi technique involves a panel of experts who participate in repeated questioning (Dalkey & Helmer, 1963) for the purposes of gathering useful (Costello & Rutherford, 2019, p. 1), agreed-upon information.…”
Section: Methodsmentioning
confidence: 99%
“…Intention to engage in water conservation efforts may be influenced by the feeling that participation in water conservation practices are optional, but that the public also needs strong government influence to increase conservation (Nolte et al, 2013). Effective extension educators and policymakers should be aware of this cognitive dissonance that can be used to drive participation in water conservation (Terry & Osborne, 2015).…”
Section: Recommendationsmentioning
confidence: 99%
“…For example, since Republicans are more inclined to react to increases in negative government perception, the programs should be implemented with appropriate amounts of pressure to encourage conservation from Republicans. Moreover, Extension educators should be aware of policymakers' political affiliation so that when they are working with them they can enhance communication effectiveness (Terry & Osborne, 2015).…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive educational programs are provided by Extension educators and promoted through collaborative efforts made between the local, state, and federal government (Terry & Osborne, 2015). Extension educators strive to provide the public with quality research to assist in developing informed decisions on critical issues at all levels.…”
Section: Introductionmentioning
confidence: 99%